Additional Treatments to the Local tumour for metastatic prostate cancer-Assessment of Novel Treatment Algorithms (IP2-ATLANTA): protocol for a multicentre, phase II randomised controlled trial. Issue 2 (25th February 2021) - Connor, Martin John; Shah, Taimur Tariq; Smigielska, Katarzyna; Day, Emily; Sukumar, Johanna; Fiorentino, Francesca; Sarwar, Naveed; Gonzalez, Michael; Falconer, Alison; Klimowska-Nassar, Natalia; Evans, Martin; Naismith, Olivia Frances; et al.
Abstract : Introduction: Survival in men diagnosed with de novo synchronous metastatic prostate cancer has increased following the use of upfront systemic treatment, using chemotherapy and other novel androgen receptor targeted agents, in addition to standard androgen deprivation therapy (ADT). Local cytoreductive and metastasis-directed interventions are hypothesised to confer additional survival benefit. In this setting, IP2-ATLANTA will explore progression-free survival (PFS) outcomes with the addition of sequential multimodal local and metastasis-directed treatments compared with standard care alone. Methods: A phase II, prospective, multicentre, three-arm randomised controlled trial incorporating an embedded feasibility pilot. All men with new histologically diagnosed, hormone-sensitive, metastatic prostate cancer, within 4 months of commencing ADT and of performance status 0 to 2 are eligible. Patients will be randomised to Control (standard of care (SOC)) OR Intervention 1 (minimally invasive ablative therapy to prostate±pelvic lymph node dissection (PLND)) OR Intervention 2 (cytoreductive radical prostatectomy±PLND OR prostate radiotherapy±pelvic lymph node radiotherapy (PLNRT)). Metastatic burden will be prespecified using the Chemohormonal Therapy Versus Androgen Ablation Randomized Trial for Extensive Disease (CHAARTED) definition. Men with low burden disease in intervention arms are eligible for metastasis-directed therapy, in the form of stereotactic ablative body radiotherapy (SABR) or surgery. Standard systemic therapy will be administered in all arms with ADT±upfront systemic chemotherapy or androgen receptor agents. Patients will be followed-up for a minimum of 2 years. Primary outcome: PFS. Secondary outcomes include predictive factors for PFS and overall survival; urinary, sexual and rectal side effects. Embedded feasibility sample size is 80, with 918 patients required in the main phase II component. Study recruitment commenced in April 2019, with planned follow-up completed by April 2024. Ethics and dissemination: Approved by the Health Research Authority (HRA) Research Ethics Committee Wales-5 (19/WA0005). Study results will be submitted for publication in peer-reviewed journals. Trial registration number: NCT03763253 ; ISCRTN58401737